Unplugged Coding-Based PBL for Enhancing Computational and Critical Thinking in Elementary Science - Ni Komang Tessya Handriyani Putri; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2026)
A problem encountered in science learning in elementary schools is students' low problem-solving skills. The purpose of this study was to determine the effectiveness of the unplugged coding-based PBL learning model on computational thinking and critical thinking skills in fifth-grade students' science subjects. This quantitative study used a nonequivalent pretest-posttest control group design. The sample size was 46 students. Data collection used descriptive tests on computational thinking and critical thinking. The data analysis technique used was the MANOVA test, followed by the LSD (Least Significant Difference) test. Data analysis was performed using the N-Gain test to assess improvements in computational thinking and critical thinking skills. Based on the results of the hypothesis test using MANOVA, the F-value for Hypothesis 1 was 27.651 and Hypothesis 2 was 9.955, both of which were greater than the F-value of 4.06 at a 5% significance level. The respective significance values were 0.001 and 0.003 (Sig. <0.05). Meanwhile, the test of hypothesis 3 using MANOVA obtained an Fcount of 15.554 and an F table of 4.06, with a significance value of 0.001. The significance value is less than the significance level (Sig. <0.05). Further testing using the LSD test obtained significance values of 0.001 and 0.003, both of which are less than the significance level (Sig. <0.05). Therefore, it can be concluded that the use of the PBL model based on unplugged coding is effective in improving students' computational thinking and critical thinking skills in fifth-grade science subjects in elementary schools.